Ansiedad preoperatoria y el nivel de dolor postoperatorio agudo en pacientes sometidas a histerectomía total abdominal - Acevedo Ramos, Amalia Elizabeth (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
Total abdominal hysterectomy is one of the surgeries that causes high postoperative pain and anxiety related to the surgical procedure; anesthetic management of these patients is carried out in most cases with neuraxial anesthesia combining local anesthetics with opioids. Objective: To determine the relationship between preoperative anxiety and the level of acute postoperative pain in patients undergoing total abdominal hysterectomy at the Regional General Hospital No. 1 of the IMSS in Charo, Michoacán. Material and methods: This were an observational, descriptive and longitudinal study carried out in 2021 with patients who met the inclusion criteria. Prior to surgery, the Preoperative Anxiety Scale (APAIS) was applied and sociodemographic variables were recorded. Surveillance was continued at 4, 6, 12 and 24 hours in search of pain with Visual Analogue Scale. Data were processed with STATA 17 software applying linear correlation and chi square tests with statistical significance p= <0.05. Results: 60 patients with an average age of 43 years were included, anesthetic management was with neuraxial anesthesia, 12 patients had a positive result for anxiety (20%), a linear correlation test was applied between anxiety and pain level at the 4, 6, 12 and 24 hours with a value of p= 0.73, 0.49, 0.0001 and 0.0741 respectively. Conclusions: The correlation was positive between the presence of preoperative anxiety and the level of postoperative pain at 12 hours. It is suggested to repeat the study controlling the drugs and doses used.

La histerectomía total abdominal es una de las cirugías causantes de un alto dolor postoperatorio y ansiedad relacionada al procedimiento quirúrgico; el manejo anestésico de estas pacientes se lleva a cabo en la mayoría de los casos con anestesia neuroaxial combinando anestésicos locales con opioides. Objetivo: Determinar la relación entre ansiedad preoperatoria y el nivel de dolor postoperatorio agudo en pacientes sometidas a histerectomía total abdominal en el Hospital General Regional No. 1 del IMSS en Charo, Michoacán. Material y métodos: Se trató de un estudio observacional, descriptivo y longitudinal realizado en el año 2021 con pacientes que cumplieron los criterios de inclusión. Se aplicó previo a cirugía escala de ansiedad preoperatoria (APAIS) y se registraron variables sociodemográficas, se continuó vigilancia a las 4, 6, 12 y 24 horas en búsqueda de dolor con Escala Visual Análoga. Los datos fueron procesados con software STATA 17 aplicando pruebas de correlación lineal y chi cuadrada con significancia estadística p= <0.05. Resultados: se incluyeron 60 pacientes con un promedio de edad de 43 años, el manejo anestésico fue con anestesia neuroaxial, 12 pacientes tuvieron un resultado positivo para ansiedad (20%), se aplicó prueba de correlación lineal entre ansiedad y nivel de dolor a las 4, 6, 12 y 24 horas con valor de p= 0.73, 0.49, 0.0001 y 0.0741 respectivamente. Conclusiones: La correlación fue positiva entre la presencia de ansiedad preoperatoria y el nivel de dolor postoperatorio a las 12 horas. Se sugiere repetir el estudio controlando los fármacos y dosis utilizados.
Facultad de Ciencias Médicas y Biológicas. Instituto Mexicano del Seguro Social. Especialidad en Anestesiología
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16390; info:eu-repo/classification/cti/3; FCMB-E-2023-0582; Histerectomía; Dolor postoperatorio; Opioides